2017
DOI: 10.20473/amnt.v1i1.5156
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Teknik, Frekuensi, Durasi Menyusui dan Asupan Energi dengan Berat Badan Bayi Usia 1-6 Bulan di Puskesmas Tasikmadu Kabupaten Karanganyar

Abstract: ABSTRAKLatar Belakang: Berat badan merupakan indicator pertama dalam menilai pertumbuhan bayi. Upaya untuk meningkatkan berat badan bayi diperlukan gizi yang maksimal dan ASI merupakan makanan utama bagi bayi terutama pada usia 1-6 bulan. Tujuan: Penelitian ini bertujuan untuk mengnalisis faktor yang berkaitan dengan pemberian ASI dan dilihat pencapaian berat badan. Faktor yang dimaksud meliputi teknik, frekuensi, durasi menyusui dan asupan enegi dengan berat badan bayi usia 1-6 bulan. Metode: Desain dalam pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 2 publications
1
10
1
7
Order By: Relevance
“…Non-fluent breastfeeding can result in nutritional deficiencies in infants (Kuntarti, Wuryanto and Ratnaningsih, 2011). A research confirmed that statement showing that there is a significant relationship between breastfeeding techniques and the malnutrition incidence in infants (1-6) months at the Tasikmadu Primary Healthcare Center in Karanganyar Regency (Sari & Tamtomo, 2017). Thus, it can be concluded that breastfeeding techniques have a crucial impact on the nutritional status of infants (0-12) months.…”
Section: Methodssupporting
confidence: 58%
See 2 more Smart Citations
“…Non-fluent breastfeeding can result in nutritional deficiencies in infants (Kuntarti, Wuryanto and Ratnaningsih, 2011). A research confirmed that statement showing that there is a significant relationship between breastfeeding techniques and the malnutrition incidence in infants (1-6) months at the Tasikmadu Primary Healthcare Center in Karanganyar Regency (Sari & Tamtomo, 2017). Thus, it can be concluded that breastfeeding techniques have a crucial impact on the nutritional status of infants (0-12) months.…”
Section: Methodssupporting
confidence: 58%
“…The univariate analysis showed that most participants in the case group did not apply breastfeeding techniques correctly since most of them (75.5%) were reported as having bad breastfeeding techniques in a comparison with the control group (40.8%). A study affirmed this result showing that most participants with a percentage of 73.9% had bad breastfeeding techniques compared to mothers (26.1%) who had good breastfeeding techniques (Sari & Tamtomo, 2017).…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…These results are in line with the study conducted by Pamuji et al, (21), which found that there were differences in prolactin hormone levels and breast milk volume in primiparous postpartum mothers after being given a combination of woolwich massage and endorphine massage compared to the control group. The same finfing was conveyed by Kusumastuti et al,(22) that the administration of a combination of woolwich massage and oxytocin massage was proven to increase breast milk production 17% higher than the control group.…”
Section: Resultsmentioning
confidence: 76%
“…Pendapatan keluarga adalah faktor yang dapat memengaruhi pemenuhan nutrisi ibu dan bayi, karena jika pendapatan keluarga lebih rendah akan sulit untuk memenuhi kebutuhan gizi ibu menyusui dan dapat menyebabkan penurunan produksi ASI. Dengan demikian, kebutuhan ASI untuk bayi tidak dapat dipenuhi secara memadai dan dapat menyebabkan berat badan anak bertambah (Sari, Tamtomo, & Anantayu, 2017).…”
Section: Istiadhatul Arzakiyah Apriliani Yulianti W Sri Wahyuni Tuunclassified